Profil Terapi dan Efek Samping Anti Tuberkulosis pada Pasien AIDS Rawat Inap - Claudia Tiffany; Didik Hasmono; Agus Sunarko (MPI (Media Pharmaceutica Indonesiana), 2019)
AIDS is a global problem, including in Indonesia. AIDS patients are easy to get pulmonary tuberculosis. These patients will receive polypharmacy which require special attention to ensure patient safety. The objective of this study is to examine the usage patterns of anti-tuberculosis therapy in AIDS patients related to types, route, dose, and see whether there are any side effects during anti-tuberculosis use. This was observational and retrospective study using patient medical record, conducted at dr. Saiful Anwar hospital, Malang in the period of April-Mei 2016. Based on medical record of 36 AIDS patients with pulmonary TB, 22 patients (61%) were in the intensive phase of treatment anti-tuberculosis cate–gory I, 8 patients (22%) in the treatment of the intensive phase of category II, 2 patients (6%) in the continuation phase category I, 1 patient (3%) was in the intensive phase of category I then get a special conditions regimen of anti-tuberculosis therapy, 1 patient (3%) was in the intensive phase category II but underwent a change to the intensive phase of MDR-TB, and other 1 patient (3%) was get the intensive phase of special conditions. Drug related problems that identified were rash (6%), Steven Johnson syndrome (3%), drug induced hepatitis due to anti-tuberculosis (22%), and jaundice without other cause (3%).